Credit, markets, and the agrarian economy of colonial India - Bose, Sugata (New York : Oxford University Press, 1994)
Contributed articles.
Includes bibliographical references.
Keywords: Agriculture -- Economic aspects -- India -- Andhra Pradesh; Peasants -- India -- Andhra Pradesh; Social classes -- India -- Andhra Pradesh